THE DEVELOPMENT OF AN ENGLISH INSTRUCTIONAL MODEL BASED ON THE INTERACTIVE AND EXTENSIVE READING APPROACHES TO ENHANCE CRITICAL READING ABILITY OF HIGH SCHOOL STUDENTS IN DEMONSTRATION SCHOOLS - Rerg-a-nun, Apinphorn; Meejang, Areerug; Thuakthong, Winit; Pupipat, Apisak (Journal of Social Science and Cultural, 2023)
The purposes of this mixed methods study were to 1) investigate the current conditions of teaching reading to senior Demonstration School students, 2) develop and verify the quality of an English instructional model based on the interactive and extensive reading approaches to enhance critical reading ability of senior Demonstration School students, 3) try out the model, and 4) improve the model. The qualitative data were gathered through interviews with teachers and students, and the sample was purposive sampling. The quantitative data were collected using a handbook evaluation form and a test on critical reading ability administered to a sample of 37 tenth-grade Patumwan Demonstration School students obtained by using multistage sampling. The data were analyzed using mean, standard deviation, T-test, and content analysis from the interviewees’ opinions on learning activities. The results revealed that the developed English instructional model consisted of 5 steps including 1) arousing interest 2) preparation of the knowledge 3) interactive reading 4) conclusion and evaluation 5) expanding knowledge. The post reading test scores were significantly higher than the pre-test scores at .05 level. The results of students’ comments found that their critical reading ability has improved through a variety of learning activities which allowed them to think critically while reading texts of their interest. Teacher’s comments found that most students paid attention and cooperated well in the learning activities.